The Influence of Training on Employee Performance in PT. Pelni (Persero) Jakarta - Faif Yusuf; Marlina Rahmi Shinta; Sonny Fransisco (Journal of Research in Business, Economics, and Education, 2020)
This study aims to determine whether there is an influence between employee training on employee performance at PT. Pelni (Persero) Jakarta. The research method in this study uses descriptive quantitative research methods using primary data. Sampling technique is a saturated sample of 50 people through a questionnaire. Processing data using SPSS 26 statistical applications. In the study obtained a large correlation coefficient of 0.838 shows a very strong relationship between training with employee performance at PT. Pelni (Persero) Jakarta. Based on the determination coefficient (R2) of 0.702, it shows that the training variable (X) affect the performance of employees (Y) by 70.2% and the remaining 29.8% is influenced by other variables. While the regression equation is obtained Y = 7.265 + 0.816X.